A Five-Level H-Bridge STATCOM for an Off-Grid PV Solar Farm under Two Controllers PI and PIλ-MPC Hybrid - Onur Ozdal Mengi (International Journal of Photoenergy)
Investigations were presented in order to eliminate the reactive power on microgrid loads fed by an off-grid and mid-power photovoltaic solar energy system (PVSES) with a static synchronous compensator (STATCOM) device. The electric network is specifically characterized by P-Q loads, ambient temperature, and widely variable solar radiation levels. Two main innovations are developed. Firstly, the STATCOM apparatus is a 5-level H-bridge inverter with capacitances as load and must totally compensates the reactive power in the network load. Secondly, this compensation is controlled by a set of fractional PI (PIλ) and model predictive control (MPC) hybrid. The efficiencies of these controllers were compared with classical PI controllers. Large simulations, without and with reactive power compensation, in steady and transient states, are carried out to underline the merits of the presented works, by performing in the MATLAB-Simulink environment.